2021
DOI: 10.1177/00914150211040451
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Social Isolation, Multimorbidity and Multiple Role Demands Among Middle-Age Adults Based on the Canadian Longitudinal Study on Aging

Abstract: Given the increasing complexity and fluidity of parenting, caregiving, and paid work patterns, in tandem with an increased risk of multimorbidity in mid-life, this study examines the relationship between these three concurrent roles and social isolation among middle-aged persons across multimorbidity statuses. Drawing upon life course theory, we applied linear mixed models to analyze 29,847 middle-aged participants from two waves of the Canadian Longitudinal Study on Aging. Findings reveal that participants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…When controlling for various confounding factors, the prevalence of social isolation among people in poor health is 1.348-1.466 times higher than among people in good health. Previous studies have confirmed the significant relationship between social isolation and well-being [ 28 30 , 62 ], which is mutually reinforcing. The main explanatory power of the relationship lies with health being a consistent predictor in the literature.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…When controlling for various confounding factors, the prevalence of social isolation among people in poor health is 1.348-1.466 times higher than among people in good health. Previous studies have confirmed the significant relationship between social isolation and well-being [ 28 30 , 62 ], which is mutually reinforcing. The main explanatory power of the relationship lies with health being a consistent predictor in the literature.…”
Section: Discussionmentioning
confidence: 66%
“…Sleep problems [ 25 ] and internet use [ 26 , 27 ] also have an impact on social isolation. Poor self-rated health [ 28 ], a low capacity for activities of daily living [ 29 ] and multiple chronic diseases [ 30 ] have also been documented. In addition, family characteristics [ 31 ], living arrangements [ 32 ] and children [ 33 ] might be factors.…”
Section: Introductionmentioning
confidence: 99%
“…Programs that provide transportation services is an ongoing theme to promote healthy aging. A longitudinal study saw an increase in the risk of multimorbidity in 29,847 middle-aged due to social isolation [26]. The impact regarding having access to transportation can create an additive effect across the complex multidimensional interworkings in health deterioration.…”
Section: Transportationmentioning
confidence: 99%
“…This period typically coincides with the peak of their professional careers and their influential roles in society in their age group. They are often burdened with numerous responsibilities both at home and in their communities [32]. The pressing demands of their daily lives often lead them to deprioritize exercise routines, ultimately contributing to muscle loss as a consequence of insufficient physical activity.…”
Section: Introductionmentioning
confidence: 99%